Declination from Occupation Based Practice: Experience of Iranian Occupational Therapists - Mohammad Khayyatzadeh-Mahani; Afsoun Hassani-Mehraban; Mohammad Kamali; Sorour Parvizi (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: Occupation has been used as an essential core of therapy in Occupational therapy (OT) paradigm from its beginning. Besides primary emphasis of OT pioneers the OT practitioners do not care about using it yet. So, this study was aimed to explore the current method of delivering occupational therapy services among Iranian occupational therapists. Materials & Methods: The qualitative conventional content analysis with purposeful sampling was used in this study. 14 occupational therapists participated in this study. Semi structured interviews were used for data gathering. The data gathering continued until reaching data saturation. The interviews were analyzed through constant comparative analysis using MAXQDA 2007 software. Results: The interviews analysis revealed 66 codes that resulted to six sub themes and three themes including: Occupation based OT (occupation based assessment and planning -hard working circumstances for occupation based therapists), technique based OT (inattention to occupation based practice- top down approach to assessment and planning-inattention to client-centered practice) and combined occupation and techniques based OT (assessment and planning with combined approach). Conclusion: It seems that the Iranian occupational therapists have deviated from their philosophical paradigm (occupation based practice) and tended to technique based OT. Lots of possible reasons such as contextual barriers , in accepting from clients' perspective and educational challenges are considered in this issue. However, the policy makers ought to plan and supervise to solve these challenges to facilitate implementing occupation based practice.